Effect of Corporate Governance on Banking System Stability in Nigeria - Olateju, Dare John; TIJANI, Bisi Riliwan (International Journal of Business Studies, 2024)
The study focused on the effect of corporate governance (CG) on banking system stability in Nigeria. The purpose of this study was to assess the effect of corporate governance on banking system stability. Data used for this study were secondary data collected from the audited annual report of 13 listed deposit money banks in Nigerian for the period of eight (8) years, the data was analyzed using STATA 14 and hypotheses were tested using random effect regression with respect to the Breusch and Pagan Lagrangian multiplier test and Hausman specification test. From the random effect regression analysis table, the results show that board size, ratio of male- female, board committee, the number of board meeting have contributed insignificantly to our model while the overall hypothesis also show an insignificant effect on CG and banks’ stability. The study recommends that since the variables used in this study have no significant effect on the banking system stability, emphasis should be shifted from these variables to other corporate governance variables. The study also suggested that More research on the study variable should be undertaken in Nigeria, this would throw more weight on the importance of corporate governance in ensuring banking system stability on a larger scale by incorporating all the deposit money banks in Nigeria.